2018
DOI: 10.1002/mpr.1717
|View full text |Cite
|
Sign up to set email alerts
|

Female–male differences in alcohol dependence levels: Evidence on newly incident adolescent and young‐adult drinkers in the United States, 2002–2014

Abstract: In the United States, there is female excess in ADS levels measured soon after drinking onset in early adolescence. The traditional male excess is seen when drinking onset occurs after mid-adolescence. Evidence from other countries will be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…A study by Cheng and Anthony conducted between 2006 and 2014 assessed the dates of first full drink and first heavy drinking episode in around 33,000 females and males (ages 12 to 21) in the United States who had their first heavy drinking episode within the past 24 months. 15 Their findings revealed that, among adolescents who started to drink between ages 11 and 14, females progressed to a heavy drinking episode more quickly than males. This suggests that when drinking starts before age 15, females are at greater risk than males of progressing to a heavy drinking episode.…”
Section: Sex Differences In Stress Factors Early Onset Alcohol Misusmentioning
confidence: 98%
See 1 more Smart Citation
“…A study by Cheng and Anthony conducted between 2006 and 2014 assessed the dates of first full drink and first heavy drinking episode in around 33,000 females and males (ages 12 to 21) in the United States who had their first heavy drinking episode within the past 24 months. 15 Their findings revealed that, among adolescents who started to drink between ages 11 and 14, females progressed to a heavy drinking episode more quickly than males. This suggests that when drinking starts before age 15, females are at greater risk than males of progressing to a heavy drinking episode.…”
Section: Sex Differences In Stress Factors Early Onset Alcohol Misusmentioning
confidence: 98%
“…Recent studies have shown that girls who report a history of abuse before adulthood are more vulnerable to developing AUD. 15 Other studies have found that adolescents who face a number of negative life events show increased levels of drug use (and misuse) compared to those who do not face these adverse events. 7,10 Exposure to early life stress may be especially harmful for women, who are exposed to more high-impact trauma (e.g., sexual abuse) than men are, and at a younger age.…”
Section: Sex Differences In Stress Factors Early Onset Alcohol Misusmentioning
confidence: 99%
“…Furthermore, women progress more quickly from regular drinking to intoxication to first experiencing alcohol problems and appear to go from loss of control over drinking to experiencing their "worst" alcohol problems more rapidly than men (Randall et al, 1999). Women with an AUD diagnosis are more likely to have shorter drinking histories compared to their male counter-parts seeking treatment (Cheng & Anthony, 2018). Conceivably, motivation for alcohol use may more quickly shift from using it for the positive effects of alcohol to using alcohol for negative reinforcement among women.…”
Section: Figurementioning
confidence: 99%
“…In humans, alcohol use during adolescence increases the risk of developing AUD in adulthood; interestingly, this occurs in an age- and sex-dependent manner. For example, an earlier age of onset (during adolescence) increases the risk of AUD in females, while late-adolescent age of onset increases risk of AUD in males [ 72 ]. In the current study, we showed dysregulation of KOR function in early-AIE-exposed females and late-AIE-exposed males.…”
Section: Discussionmentioning
confidence: 99%